Temporal patterns of alcohol consumption and attempts to reduce alcohol intake in England. (December 2016) - de Vocht, Frank; Brown, Jamie; Beard, Emma; Angus, Colin; Brennan, Alan; Michie, Susan; Campbell, Rona; Hickman, Matthew
Abstract Background The Alcohol Toolkit Study (ATS) is a monthly survey of approximately 1700 adults per month aged 16 years of age or more in England. We aimed to explore patterns of alcohol consumption and motivation to reduce alcohol use in England throughout the year. Methods Data from 38, 372 participants who answered questions about alcohol consumption (March 2014 to January 2016) were analysed using weighted regression using the Rsurvey package. Questions assessed alcohol consumption (AUDIT-C) and attempts to reduce consumption. Results Sixty-seven percent of participants reported using alcohol, with a small negative trend of about 2 % reduction over 12 months in the studied period (P < 0.01). These include 25 % higher risk drinkers and 10 % regular binge drinkers. About 20 % of higher risk drinkers indicated they were attempting to reduce their alcohol consumption. Attempts were lowest in December (−20 %; 95 % CI 0–35 %), but increases significantly in January (+41 %; 95 % CI 16–73 %) compared with other months (P < 0.001), indicating a small net gain; at least in attempts to reduce. However, there was no evidence that the increased motivation in January was accompanied by a reported decrease in consumption or binge drinking events. This could be an artefact of the use of AUDIT questions, but could also reflect a disconnect between attempting to reduce alcohol consumption and subsequent change; maybe as a result of lack of continuing support. Conclusions January is associated with moderate increased attempts to reduce alcohol consumption. However, we find little evidence of a change in alcohol consumption. In part, this may be due to temporal insensitivity of the AUDIT questions.